An audit of routine grey scale sonograghic imaging for pelviureteric junction obstruction: Do they identify lower polar vessels? - Chapman Stephen; Kumar G; Chandran Harish (Wolters Kluwer Medknow Publications, 2010)
Background: Aberrant lower polar vessels are uncommon causes of pelviureteric junction (PUJ) obstruction. Preoperative identifi cation would help in planning the appropriate procedure. We attempted to determine whether routine investigations would predict crossing lower polar vessels. Materials and Methods: This was a retrospective study of 20 patients that either had ultrasonographic investigation by a radiologist who was blinded to the aetiology of PUJ obstruction, or underwent minimal access surgery for PUJ obstruction, from 2005 to 2007, in the Birmingham Children′s Hospital, UK. Results: There were 20 patients with PUJ obstruction, 8 were found at operation to have crossing lower polar vessels causing PUJ obstruction. The sonography correctly identifi ed crossing vessels in only one, with a sensitivity of 12.5%, specifi city of 66.6%, positive predictive value of 20%, and negative predictive value of 53%. Conclusion: Preliminary results showed that none of these investigations could reliably identify lower polar vessels.